Towards a More Resilient Healthcare Sector in Post-COVID-19 Pandemic in Jordan - Mowafi, Omar; Al-Hasan, Melina; Khamees, Basheer A.; AL Hasan, Rima; Al-Zu’bi, Zu’bi M.F.; Al Kurdi, Barween (International Review of Management and Marketing, 2024)
This study explores the desirable conditions for the Health Sector Governance in post-COVID-19 pandemic Jordan. A primary qualitative approach was used with semi-structured interviews carried out with eighteen public sector doctors and hospital managers in Jordan. The results of the study indicate that there is a need for the health care sector of Jordan to be improved through governance change. Moreover, there is a need for rapid communication between stakeholders, fast financial decision-making processes, establishment of pandemic-specific emergency rooms, more coordination between public and private health sectors, a national health care database, and a system for emergency classification in hospitals. This would help in ensuring that immediate measures are taken which are focused on the providing immediate care to patients.